Adaptação transcultural e validação do instrumento Parental Health Literacy Activities Test (PHLAT) - Simch, Francielle Brustolin de Lima (2020)
Childhood illness is a factor that impacts a child's life, in view of changes in health and well-being conditions, changes in their routine and family, age-specific vulnerability, often associated with the family's social vulnerability. In this sense, when the family seeks help from the health teams to meet the care demands of their sick child, efficient communication between health professionals and caregivers/family members is important, in order to keep them informed and oriented about the treatment, procedures, therapy and doubts about caring. To assess whether this communication is being effective in daily practice, there is a need for assessment instruments that can measure the level of health literacy of caregivers/family members of children, who seek health care in primary care. However, the assessment instruments, widely used abroad, are not available for this population in Brazil, although they are already used for other age groups and following chronic conditions and therapeutic adherence. Thus, starting from instruments that allow cross-cultural attunements, adapting the existing instrument to the local reality, makes it possible to fill this gap. The aim, then, is to carry out the translation, cultural adaptation, psychometric validation and application of the instrument Parental Health Literacy Activities Test (PHLAT), for caregivers/family members who seek care in the primary care unit. The study is outlined as a methodological, quantitative study, following the steps of translation, synthesis, back-translation, analysis by a committee of judges, pre-test, test/retest and application of statistical tests to assess psychometric properties and obtain its version for Brazilian Portuguese. The pretest was carried out with a sample of 31 family members, the test and retest with 93 and for clinical validation it was applied to 302 family members, according to the sample calculation. It was developed in primary care units in the municipality of Toledo, PR. Inferential statistical analysis was applied to verify the validity and reliability of the instrument for the phases performed. In the content validity assessment carried out by the panel of judges, an adequate agreement rate for the translation consensus of 100% was observed. In the assessment of reliability after the application of the instrument in the pre-test, the internal consistency measured by Cronbach's Alpha was 0.73 and, in the test-retest it was 0.69. The assessment of the instrument's reliability regarding stability, measured by the intraclass correlation, was 0.865, with a 95% confidence interval, both demonstrating substantial reliability. The instrument was considered adequate for its cultural adaptation and validation for Brazilian Portuguese, and reliable for application among caregivers/family members. In clinical validation, the construct validity measured by confirmatory factor analysis demonstrated equivalence of the instrument with the original, remaining in a single dimension, reliability was measured by Kuder-Richardson with a value of 0.70. 67.4% of the participants answered the PHLAT questions according to the expected, so most caregivers had satisfactory functional health literacy. However, only 39.7% were able to prepare a bottle for oral rehydration and 42.1% would give the purchased medicine at the pharmacy on their own to the child; 37.1% were able to read a thermometer correctly to determine whether to call the pediatrician after receiving a specific temperature to use as a parameter for fever. Thus, 97.7% correctly interpreted information on the specificity of the medication contained in the offered box, 87.1% responded adequately regarding the correct time between intervals between feedings after receiving a brochure with guidelines on breastfeeding. Mothers (92.4%) were identified as the main caregivers. High school completed 53.6% and 24.5% higher education/graduate. The prevalent income was up to two minimum wages. The average age of caregivers was 28.3 years and 55.3% reported looking exclusively at the primary care unit for child health care. Higher income and more years of schooling influenced better health literacy results. In this way, the study contributes with a reliable instrument for verifying Health Literacy for family members of children under one year old, unprecedented in Brazil, useful for primary care professionals, making it possible to measure the level of understanding of families about therapeutic and health guidelines. care received. Thus, the lack of adequate literacy is a collective adversity, however in child health it is necessary to stimulate communication clearly between the health team as a measure to face this reality, reducing the negative impacts on the child's health conditions.